2014
DOI: 10.1016/j.jacc.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Drug-Eluting Balloon Versus Everolimus-Eluting Stent in Patients With Bare-Metal Stent–In-Stent Restenosis

Abstract: In patients with BMS-ISR, both DEB and EES provided excellent clinical results with a very low rate of clinical and angiographic recurrences. However, compared with DEB, EES provide superior late angiographic findings. (Restenosis Intra-stent of Bare Metal Stents: Paclitaxel-eluting Balloon vs. Everolimus-eluting Stent [RIBS V]; NCT01239953).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
91
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(99 citation statements)
references
References 25 publications
4
91
2
Order By: Relevance
“…A direct randomized comparison between the paclitaxel-eluting balloon and EES for the treatment of BMS restenosis was performed by the Restenosis Intra-Stent of Bare Metal Stents: Paclitaxel-Eluting Balloon Versus EverolimusEluting Stent (RIBS V) investigators. 8 The results of this study were different from the one reported here. Although the late losses of the DEB groups were similar (0.09 mm in the current study and 0.14 mm in RIBS V), the late loss after EES treatment was much higher in the present study (0.44 versus 0.04 mm in RIBS V).…”
Section: See Article By Pleva Et Alcontrasting
confidence: 99%
See 1 more Smart Citation
“…A direct randomized comparison between the paclitaxel-eluting balloon and EES for the treatment of BMS restenosis was performed by the Restenosis Intra-Stent of Bare Metal Stents: Paclitaxel-Eluting Balloon Versus EverolimusEluting Stent (RIBS V) investigators. 8 The results of this study were different from the one reported here. Although the late losses of the DEB groups were similar (0.09 mm in the current study and 0.14 mm in RIBS V), the late loss after EES treatment was much higher in the present study (0.44 versus 0.04 mm in RIBS V).…”
Section: See Article By Pleva Et Alcontrasting
confidence: 99%
“…The initial strategy to perform plain balloon angioplasty to treat bare-metal in-stent restenosis (ISR) was inadequate, leaving the remaining options of implanting a drug-eluting stent or using a drug-eluting balloon (DEB). [1][2][3][4] Pleva et al 5 report, in this issue of Circulation: Cardiovascular Interventions, the results of a study randomizing 136 patients with bare-metal ISR to treatment with a DEB (Sequent Please; B. Braun AG, Melsungen, Germany) or an everolimus-eluting stent (EES; Promus Element; Boston Scientific, Marlborough, MA. )…”
mentioning
confidence: 99%
“…Patients with small vessels (≤2.0 mm in diameter), long lesions (>30 mm in length), or total occlusions (Thrombolysis in Myocardial Infarction [TIMI]=0) were excluded. 16,17 Likewise, patients with early (<1 month) ISR, those presenting as an acute myocardial infarction, or showing a large thrombus on angiography were excluded. However, patients with recurrent ISR and those with edge-ISR were eligible.…”
mentioning
confidence: 99%
“…Whenever underexpanded stents were identified, aggressive high-pressure dilations with noncompliant balloons were recommended. 16,17 Patients allocated to EES (Xience Prime, Abbott Vascular, IL) were treated using a 1.1:1 balloon:artery ratio and high (>14 bar) pressures. Systematic postdilation with noncompliant balloons at high pressures was recommended but eventually left to the operator's discretion according to procedural results.…”
mentioning
confidence: 99%
See 1 more Smart Citation